Evaluation of the plastic injection machine maintenance system through the TOPSIS method - Calvillo, Jesús Manuel (2019)
The following document talks about the parameters of the maintenance system implemented in plastic injection machines of a maquiladora company located in Ciudad Juarez Chihuahua. The method used in this investigation is essentially ulti-criteria decision making, the technique for the order of preference for similarity to the ideal TOPSIS solution. Therefore, an evaluation of the maintenance system is carried out, using measurable collected in said company. With this evaluation the plastic injection machine is determined in better conditions, as well as the machine in worse conditions, which helps management to make better decisions regarding each machine. The objective of this research is to address the study of decision-making in the industrial field specifically in the maintenance system of plastic injection molding machines.